Transforming Vocational Education Pedagogy: Integrating Extended Reality and Problem-Immersive Experiences to Foster 21st-Century 6C Competencies - Wulansari, Rizky Ema; Candra, Oriza; Samala, Agariadne Dwinggo; Safitri, Rahmadona; Tin, Chau Trung; Sakti, Rizki Hardian (Journal of Technical Education and Training, 2025)
According to the hotly debated issues in vocational education, it is challenged to develop the 21st century competencies especially the 6Cs namely critical thinking, creativity, collaboration, communication, citizenship, and character in the face of the fast-changing technology. The classical pedagogic models are not usually able to help keep the learners interested in the real-life immersive situations that reflect industrial practice. This research will revolutionize the vocational education learning process by incorporating into it Extended Reality (XR) and problem-immersive learning project to enhance the ability of students to master the 6C competencies. The study used quasi-experimental design and control and experimental group in exploring vocational students. Pre-test and post-test data were obtained by way of observation checklists, competency-based performance tests. To determine the effectiveness of the intervention, statistical analysis, which was done through ANCOVA, t-tests and SEM, was done. The results show that students that underwent XR-facilitated problem-immersive learning showed much higher advancements in critical thinking, collaboration and creativity as opposed to those in conventional classrooms. Besides, interactive simulations and collaborative problem-solving scenarios, placed in XR environments, promoted communication, character building, and citizenship awareness. The article concludes that the combination of XR and problem-immersive teaching provides a revolutionary route to vocational education that fulfils the requirements between the theoretical training and the real-life industrial requirements. The implications will be in the fact that educators should be developed professionally, curriculum needs to be redesigned in accordance with new technologies, and the wider implementation of XR-enriched models is necessary to equip vocational learners with the skills to work in dynamic future environments.